Amylose Accumulation Under Water Deficit in Glutinous Rice (Oryza sativa L. Var. glutinosa) - Yuli Yarwati; Nunun Barunawati; Ariffin Ariffin (AGRIVITA, Journal of Agricultural Science, 2023)
The research aims to obtain a genotype of local glutinous rice tolerant to drought stress by investigating yield and physiological responses. The experiment is conducted in May-September 2020 in West Lombok, West Nusa Tenggara. The factorial experiment uses a Randomized Block Design, including the first factor: glutinous rice varieties, namely Me'e, Kala, Samada, and Paketih. The second factor is water supply, consisting of 2,250 ml, 3,375 ml, 4,500 ml, and 5,625 ml. The variables are observed stomata density, the content of proline and chlorophyll, panicle length, number and weight of grains, starch, and amylose content. The result shows that the stomata density has about 39 to 54.74 mm2 caused by water application on all glutinous rice strains. The chlorophyll content decreases to 50% following the declining amount of water application, while proline content on all varieties reaches 40% by water supply at 2,250 ml. In addition, the amylose content reaches 40% with 4,500 ml of water and 5,625 ml of water in all varieties. By contrast, increasing the amount in water supply affect several variables observed, an increase in panicle length of around 10% and the number and weight of the grains at 20% and 40%, respectively.